2014
DOI: 10.1158/1541-7786.mcr-14-0255-t
|View full text |Cite
|
Sign up to set email alerts
|

MIF Antagonist (CPSI-1306) Protects against UVB-Induced Squamous Cell Carcinoma

Abstract: Macrophage migration inhibitory factor (MIF) is a homotrimeric proinflammatory cytokine implicated in chronic inflammatory diseases and malignancies, including cutaneous squamous cell carcinomas (SCC). To determine whether MIF inhibition could reduce UVB light–induced inflammation and squamous carcinogenesis, a small-molecule MIF inhibitor (CPSI-1306) was utilized that disrupts homotrimerization. To examine the effect of CPSI-1306 on acute UVB-induced skin changes, Skh-1 hairless mice were systemically treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Dorsal skin samples for p53 analysis were fixed in 10% neutral buffered formalin for immunohistochemical analysis as previously described . Dorsal skin samples for the myeloperoxidase and cyclobutane pyrimidine dimer assays were snap frozen in liquid nitrogen and analyzed following previously developed methods .…”
Section: Methodsmentioning
confidence: 99%
“…Dorsal skin samples for p53 analysis were fixed in 10% neutral buffered formalin for immunohistochemical analysis as previously described . Dorsal skin samples for the myeloperoxidase and cyclobutane pyrimidine dimer assays were snap frozen in liquid nitrogen and analyzed following previously developed methods .…”
Section: Methodsmentioning
confidence: 99%
“…Further analysis revealed that CPSI-1306 treatment regulates cell-cycle progression and promotes apoptosis. MIF has been reported to induce apoptosis by inhibiting p53 activation and stabilization 26,41 . In our study, it is plausible that CPSI-1306 mediates its antitumor effects by impeding MIF-dependent negative regulation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Since we observed that MIF is overexpressed in TNBC and enhance breast cancer growth and migration in vitro and in vivo, we evaluated the anticancer potency of a small-molecule chemical inhibitor of MIF to inhibit the proliferation and progression of TNBC. We used CPSI-1306, which has been reported to inhibit MIF activity 26 . A panel of human (MDA-MB-231, MDA-MB-468, SCP-2) and mouse (MVT-1) TNBC cells were treated with CPSI-1306 and cell viability was estimated by MTT assay.…”
Section: Cpsi-1306 a Small-molecule Mif Inhibitor Has Potent Antipromentioning
confidence: 99%
“…Numerous studies demonstrate that MIF contributes to tumorigenesis in colon, breast and melanoma and bladder cancer. 14,38 Although the mechanisms behind the observed MIF-mediated contribution to tumorigenesis in the above mentioned cancers are multiple, there exists some similarities and differences between these mechanisms and those of MIF mediated oral carcinogenesis. For example, in bladder cancer, MIF promotes cellular proliferation and angiogenesis, 39 mechanisms which are also important in oral carcinogenesis.…”
Section: Tumor Immunology and Microenvironmentmentioning
confidence: 99%